Analisis Pengendalian Internal Dalam Upaya Mengelola Food Cost Selama Masa Pandemi Covid- 19 Di Hotel Golden Tulip Jineng Resort Bali - I Gusti Agung Febrianto; Michael Christanta; I Putu Esa Widhaharthana (JURNAL BISNIS HOSPITALITI, 2022)
This study aims to analyze internal controls during the Covid-19 pandemic in the purchasing, receiving, storing, and issuing departments. The subjects in this study were staff who had a direct relationship with the internal control activities of food procurement, namely purchasing manager, cost control, finance manager, receiving staff and storekeeper at Golden Tulip Jineng Resort Bali. Data collection techniques used in this study were interviews, observation, and documentation studies. The data analysis technique used is data triangulation. The results of the research analysis show that controlling food and beverage costs at the Golden Tulip Jineng Resort Bali has not been implemented optimally. This is indicated by the occurrence of an adverse difference between actual food costs and standard food costs as a result of the lack of coordination carried out by the food cost control function, namely purchasing, receiving, storing, and issuing. During the Covid-19 pandemic, standard purchase specifications have not been carried out optimally.